Investigating the scientific landscape of global research on medical education related to coronavirus disease-2019 (covid-19): A bibliometric analysis and visualization - Karakose, Turgut; Yirci, Ramazan; Ozdemir, Tuncay Yavuz; Kocabas, Ibrahim; Demirkol, Murat (A. CARBONE Editore, 2021)
Introduction: This study aims to inspire researchers to conduct future studies within this subject area through a bibliometric analysis of publications that focused on COVID-19-related medical education. Materials and methods: The data of the study were obtained by determining publications from the Web of Science Core Collection (WoSCC) bibliographic database that focused on COVID-19-related medical education and then analyzed according to bibliometric methodology. VOSviewer software and visualization maps were used to report the analytical findings obtained from the collected data. Results: The findings showed that the number of publications that focused on COVID-19-related medical education increased steadily and consistently and that these publications focused on different topics such as "medical students," "telemedicine," "pandemic," "undergraduate," and "e-learning." It was determined that the United States, the United Kingdom, China, and Singapore were the top contributors to the articles published on COVID-19-related medical education and that most publications consisted of "theoretical studies." In addition, the results of this study revealed that in order to contribute to the rapid dissemination of scientific knowledge produced during the pandemic, the editorial (referee/blind review) and publication processes of journals were conducted quicker than usual for articles pertaining to COVID-19. Conclusion: This study revealed the research trends and current status of publications that focused on COVID-19-related medical education through bibliometric analysis and provided important findings for the future research vision of this subject area. To the best of the authors' knowledge, no other comprehensive bibliometric analysis of publications with a focus on COVID-19-related medical education has been conducted thus far. The current study, therefore, contributes to the knowledge base on COVID-19-related medical education by offering scientometric analysis of the existing literature and knowledge. © 2021 A. CARBONE Editore. All rights reserved.
Keywords: Bibliometric analysis; Coronavirus; COVID-19; Medical education; Visualization